Computer Programming to Estimate the Global Daily and Hourly solar Radiation of any location around the Globe - Asefa , Natnale Sitotaw (International Journal of Data Science, 2023)
Solar data collection and radiation analysis are basic to study several solar energy-related types of research. But, most researchers get difficulty while collecting such valuable data. In most developing countries and rural areas of the world, it is a bottleneck situation to get the ground-level solar radiation data. The intended purpose of this research is to develop a code that can estimate the daily and hourly variation of global solar radiation for any location around the globe. A python script is developed to make users flexible to use for any climatic region of the world. As an illustration, the developed code is implemented for three regions namely, Algeria, Pakistan, and Nigeria that researchers developed a correlation for each climatic region. The output shows that it is possible to use a computer program for any climatic region that researchers or any users want to find the estimated global daily and hourly solar radiation data.